DAMPAK KEBIJAKAN PENETAPAN HARGA ACUAN TERHADAP VOLATILITAS HARGA CABAI BESAR DI INDONESIA - Yovita Nyssa Preciosa; Setiawan Sariyoga; Ratna Mega Sari (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2019)
Red chili takes concern from various circles since its price big enough fluctuating, even would affect the inflation. This can lead to domino effect which is could be ended to the market failure. Stabilization of prices through the issuance of policies by the Government is one way to solve market failure. This research aims to analyze price volatility, and analyze the impact of policy determination of reference price for purchasing at farmer and reference price for selling at consumer on curly red chili and big red chili in Indonesia which is build using ARCH-GARCH model. Based on the results, price volatility of curly red chili was influenced by volatility one previous period and variant one previous period, while price volatility of big red chili was influenced by volatility one previous period and variant two previous period. The implementation of policy determination of reference price for purchasing at farmer and reference price for selling at consumer cause price volatility of curly red chili and big red chili after the policy constant until the end of the period of analysis.